Characteristics of soil of “Józefka” deposit overlay, Kielce District - Pękala, Michał (Geology, Geophysics and Environment, 2016)
The area of research works comprised the mining area of the Józefka mine, located in Górno – ca. 10 km eastwards from Kielce. Dolomite and calcareous deposit is exploited in the mine. It is estimated that it dates back to Givetian period (Czarnocki 1938). The obtained material is used as road aggregate. The deposit is located in the southern part of Świętokrzyskie Mountains, in the so-called Kielce zone being the component of Małopolskie Province Massif (Stupnicka 1997). Silty soils deposited in the bed were pocket and interbedding. An attempt to describe them precisely has not been taken up yet. Three samples with intact structure, natural moisture and graining were collected during field works. The deposit recognition was carried out at two stages: 1) mineral and petrographic, 2) geotechnical. In the first stage analysis includes optical microscopy of thin section, X-ray diffractometry and thermal differential analysis DTA. Clay fraction (below 2 µm) was separated by settling in water. Oriented specimens, glikoled and heated to 550 oC were analyzed. The rock contains up to 70 wt% of detrital quartz. At the second stage the research programme in accordance with the engineering practice and discipline standards was adopted (PKN-CEN ISO/TS 17892 and guidelines Building Research Institute). Basic physical parameters were designated: – natural moisture, – bulk density, – density, – granulometric composition, – plasticity and liquidity limits, – swelling index. Based on granulometric composition the tested soils were classified (as per PN-EN ISO 14688-2 standard) as silt clayey-sandy (saclSi). The results of swelling index designation classify sample 1 as highly swelling and the remaining ones as medium swelling (Niedzielski, 1993). The purpose of the project was to indicate the dependency between the diversification of mineral composition and physical properties of tested material.